Experimenting the Long-Haul Association between Components of Consuming Renewable Energy: ARDL Method with Special Reference to Malaysia - Roespinoedji, Djoko; Juniati, Sri; Hasan, Hafnida; Jalil, Nasir Abdul; Shamsudin, Mohd Farid (International Journal of Energy Economics and Policy, 2019)
Global warming is a standout amongst the present most critical environmental issues, caused generally by emission of greenhouse gases, for example, carbon dioxide from the consuming of fossil fuels. Emissions of carbon dioxide fluctuate all through nations in Asia. It is progressively perceived that nations must act to advance the more prominent utilization of renewable energy resources as a component of activities looking to relieve environmental change. This paper shows a survey of the energy request situation in Malaysia and Indonesia. In this renewable energy, resources are getting to be attractive for sustainable energy development in Malaysia. It is essential for Malaysia to build the consumption of renewable energy to lessen its reliance on dirty fossil fuels for electricity generation. This paper endeavours to examine the elements influencing renewable electricity consumption in Malaysia. In particular, our examination means to investigate the long-haul relationship among renewable electricity consumption, economic growth, CO2 emanations, foreign direct investment and exchange transparency over the period from 1980 to 2015. By utilizing autoregressive distributed lag (ARDL) bounds testing cointegration approach, we locate that financial development and foreign direct investment (FDI) are the real drivers for renewable electricity consumption. Exchange transparency, be that as it may, is found to have a negative effect on renewable electricity consumption over the long haul. Strangely, the impact of CO2 outflows on renewable electricity consumption isn’t critical. In addition, the vector error correction model (VECM) Granger causality test finds the presence of a unidirectional causality relationship running from GDP to renewable electricity consumption, affirming the legitimacy of conservation hypothesis in Malaysia. Some significant policy suggestions are likewise talked about. It is accordingly prescribed that the policymakers are required to concentrate on the green energy generation part by expanding renewable energy creation from the current sources. Keywords: Renewable electricity, consumption, GDP, Auto Regressive Distributed Bound Testing, VECM Granger causality test, Malaysia JEL Classifications: N70, F43 DOI: https://doi.org/10.32479/ijeep.8694